2008
DOI: 10.1097/mph.0b013e3181754198
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Ventilation in Immunocompromised Pediatric Patients: Eight Years of Experience in a Pediatric Oncology Intensive Care Unit

Abstract: Our results encourage the use of NPPV as a first-line treatment in children with malignancies who develops acute respiratory failure, except in those with severe hemodynamic status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
50
1
11

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 31 publications
5
50
1
11
Order By: Relevance
“…The success rate of NIV was found as 74.2% in previous studies [6]. Dohna-Schwake et al presented that NIV had a valuable impact in children with acute pulmonary insufficiency and 38% of patients practised NIV were found as failure in their study [7].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The success rate of NIV was found as 74.2% in previous studies [6]. Dohna-Schwake et al presented that NIV had a valuable impact in children with acute pulmonary insufficiency and 38% of patients practised NIV were found as failure in their study [7].…”
Section: Discussionmentioning
confidence: 83%
“…Pancera et al reported that the majority of patients with worse hemodynamic status were NIV failure [6]. A recent prospective study stated that mortality rates can be reduced in pediatric patients with NIV [18].…”
Section: Discussionmentioning
confidence: 99%
“…The values of arterial PCO2, hypoxemia, arterial pH, and respiratory rate were no different between the two groups. The study results encourage the use of NIV as the first treatment in oncologic children with respiratory insufficiency, and without hemodynamic instability (19) . Piastra et al (22) developed a prospective cohort study with 23 immunocompromised patients with ARDS admitted to the ICU of a university hospital and treated with NIV.…”
Section: Stregth Of Recommendationmentioning
confidence: 95%
“…Há apenas alguns estudos, incluindo dissertações que analisaram amostras maiores, que oscilaram entre 150 a 400 sujeitos (Hallahan et al, 2000;Dalton et al, 2003;Escobar et al, 2004;Fiser et al, 2005;Da Silva et al, 2008;Tamburro et al, 2008;Pancera et al, 2008).…”
Section: Discussionunclassified
“…Taxas de mortalidade elevadas ainda são descritas em nosso país para pacientes com câncer que desenvolvem sepse severa ou choque séptico (Escobar, 2003;Pancera et al, 2008;Da Silva et al, 2008). Tais valores são superiores quando comparados a publicações recentes, que não encontraram diferença na mortalidade por choque séptico entre crianças oncológicas e não oncológicas (Kutko et al, 2003;Fiser et al, 2005).…”
Section: Discussionunclassified